Nível de evidenciação contábil das fundações privadas do município de Belo Horizonte: uma análise das entidades de educação e pesquisa - Cleberson Luiz Santos de Paula (2011)
The accounting disclosure by the nonprofits entities is an important point to demonstrate the transparency of its management, and if made in the better possible way, it allows the identification of the social return generated. In Brazil, over the past five years, few studies related to that theme were developed in the Third Sector. Considering that the public prosecution service has as function to veil by private foundations, their annual reportings rendered to that organ should contribute to the monitoring in order to be in better way. Therefore, this research analyzes the level of accounting disclosure of the Private Foundations of the Education and Researches Area of Belo Horizonte district. To reach that objective the accounts rendered of 28 foundations which were analyzed in the period from 2006 to 2009, installments those correspondents to the public prosecution service of the State of Minas Gerais through the SICAP. Silveira (2007) were the model used to identify the disclosure level, that starting that scope from the accounting norms, it relates several aspects that should observed in the accounts rendered / reporting, making possible to identify the disclosure level and if those assist to the requirements of the accounting norm. The results are divided in three categories: profile of the analyzed entities, means of analyzed disclosure and verification of disclosure items. Related to the profile of analyzed entities it has been identified an evolution in the Total Assets and a reduction in the numbers of foundations that hired independent audit. In the means of analyzed disclosure, the Explanatory Notes and the Report of Complementary Activities were the items which presented the smallest disclosure level, 80.26% and 67.86%, respectively. The Balance Sheet and the Income Statement were evidenced in your totality. Analyzing the verification items evidenced, identified that: 1) the use of generic bills with important values in the bills of the assets, passive, revenues and expenses, and 2) the non presentation in the Explanatory Notes of the information that allow to identify the referring values the exemption of contributions fuelfare, the revenues gained with or without gratuidade and the explored fiscal benefits they were, the two items that presented smallest acting. Considering that the social return is an important point to measure the acting of those entities, any institution could make possible, through the information supplied in SICAP, the identification of that result. In general, identified a level of disclosure of 69.17%, 70.29%, 70.90% and 68.10% for the period from 2006 to 2009, respectively. In the ranking of the five "best" foundations, in terms of the level of disclosure, just one stayed in the four years of analysis in that rank, and that didn't hire service of independent audit; the same happened in the ranking of the worst five classified, and that foundation hired audit service